TRANSFORMASI PENDIDIKAN AGAMA ISLAM MELALUI INTEGRASI LITERASI DIGITAL PADA PEMBELAJARAN ABAD KE-21 - Mutiara As'syifa , Rahma; Windi Nurohmatul Azizah; Arini Alfa Auneva Tsuroyya Enha; Salsabila Rizkya Zalianty; Nailul Uly Emiliana; Nur Laila Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Advances in information technology in the modern era are driving fundamental changes in educational paradigms, including in the subject of Islamic Religious Education. Students’ low digital literacy skills, teachers’ limited competence in utilizing technology, and the continued dominance of conventional teaching methods are issues that must be addressed immediately so that Islamic Religious Education remains relevant to the demands of the times. This study aims to examine the urgency of transforming PAI learning through the integration of digital literacy, identify the challenges of its implementation, and analyze its impact on the quality of learning and character development of students in the 21st century. The study employs a qualitative approach using library research, which involves a descriptive analysis of various scientific sources including journals, books, and previous research relevant to the topic without conducting direct field data collection. The findings indicate that the integration of digital literacy into PAI instruction fosters more interactive, flexible, and contextual learning processes through the use of media such as educational videos, e-books, podcasts, and digital games. This approach has also proven to support differentiated instruction capable of accommodating the diverse needs of students. Furthermore, teachers’ digital competencies are a key determinant of the success of this transformation. However, its implementation still faces challenges, including the technological infrastructure gap between urban and rural areas, as well as ethical issues and concerns regarding the protection of personal data in the use of artificial intelligence. Collaboration between the government, educational institutions, and the community is necessary to achieve a sustainable, digital literacy-based transformation of PAI.